Integrated project delivery: the obstacles of implementation - Fish, Amanda (Kansas State University, 2011)
The purpose of this report is to provide information on Integrated Project Delivery (IPD) as a construction project delivery method and identify some of the obstacles that are limiting its implementation into the design and construction industry. This report includes a general overview of IPD and a comparison to traditional project delivery methods: Design-Bid-Build, Design-Build, and Construction Manager at Risk. The advantages of IPD and its possible positive impact on the industry is introduced followed by the three major obstacles that must be evaluated and resolved before this delivery method can begin to be embraced by the industry. The three major obstacles include: contracts, insurance, and IPD structure for facilitation. Each of these obstacles is explored in detail and solutions being successfully implemented by industry professionals are presented. Finally, conclusions about the future of IPD are presented along with future research that needs to be conducted for a better overall understanding of IPD.
Keywords: Integrated Project Delivery; IPD; Obstacles; Implementation; Architectural engineering (0462); Engineering (0537)